3D Fabrication of 2D Mechanisms. (May 2015) - Hergel, Jean; Lefebvre, Sylvain
Abstract The success of physics sandbox applications and physics‐based puzzle games is a strong indication that casual users and hobbyists enjoy designing mechanisms, for educational or entertainment purposes. In these applications, a variety of mechanisms are designed by assembling two‐dimensional shapes, creating gears, cranks, cams, and racks. The experience is made enjoyable by the fact that the user does not need to worry about the intricate geometric details that would be necessary to produce a real mechanism. In this paper, we propose to start from such casual designs of mechanisms and turn them into a 3D model that can be printed onto widely available, inexpensive filament based 3D printers. Our intent is to empower the users of such tools with the ability to physically realize their mechanisms and see them operate in the real world. To achieve this goal we tackle several challenges. The input 2D mechanism allows for some parts to overlap during simulation. These overlapping parts have to be resolved into non‐intersecting 3D parts in the real mechanism. We introduce a novel scheme based on the idea of including moving parts into one another whenever possible. This reduces bending stresses on axles compared to previous methods. Our approach supports sliding parts and arbitrarily shaped mechanical parts in the 2D input. The exact 3D shape of the parts is inferred from the 2D input and the simulation of the mechanism, using boolean operations between shapes. The input mechanism is often simply attached to the background. We automatically synthesize a chassis by formulating a topology optimization problem, taking into account the stresses exerted by the mechanism on the chassis through time.